Uma nova (?) fórmula para o cálculo de rações - Torres, A. P. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1949)
Looking for a short and quick method for calculating animal ration, the Author deduces and presents a formula which gives the amount of a particular food to be added to the mixture for a balanced diet. The necessity of proper tables to facilitate the use of the formula is pointed out.